Effects of Erythrina poeppigiana pruning residues on soil organic matter in organic coffee plantations - Payan Zelaya, Fidel A. (CATIE, Turrialba (Costa Rica) University of Wales, Bangor (RU). School of Agricultural and Forest Sciences, 2014)
Tesis (Ph. D.) - CATIE-UWB, Turrialba (Costa Rica), 2005